Analisis Persepsi Konsumen Terhadap Bauran Pemasaran pada Produk UMKM Lupba - Putri, Nadhifa Kartika; Hapsari, Hepi (Universitas Galuh, 2024)
This research aims to find out how consumers perception the aspect of marketing mix in UMKM Lupba products. This study was conducted from January to February 2024. The data used in this study were primary data obtained from interviews with consumers using questionnaires to 100 respondents and secondary data obtained from internets using Google Scholar. The results show that consumers' perception of the mixed aspects of product marketing in UMKM Lupba products is very high and the mix of marketing prices, places, and locations in UMKM Lupba products is high.